2017
DOI: 10.15678/eber.2017.050303
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Strategic Partnerships in the Internationalisation of Small Born Global Firms

Abstract: A B S T R A C T Objective:The article discusses motives driving the internationalisation of small born global firms and explores the role strategic partnerships play in the process. It argues that born globals are forced into international markets soon after their foundation due to limited domestic market capacity. Furthermore, they attempt to prevent competition on international markets and secure first mover advantages. Research Design & Methods:Based on primary data gathered in the course of interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
(200 reference statements)
2
6
0
Order By: Relevance
“…Overall, the statistical analysis has shown that SMEs' profitability resulted from international operations (Profits_int variable) and the development of foreign markets where the organization is present (Markets_int variable) are highly correlated with the use of strategic collaborators (Collaborators variable), while the use of intermediaries (Intermediaries variable) correlates solely with the profitability achieved through international operations (Profits_int variable). The current findings are mostly in line with previous research contending the important role of strategic collaborators and intermediaries in achieving profitability at the international level in the case of SMEs (Swoboda, Meierer, Foscht & Morschett, 2011;Capik & Brockerhoff, 2017;Vătămănescu et al, 2020 a, b, c;Vătămănescu et al, 2021). The same applies to the correlation between strategic collaborators and SMEs development on the foreign markets (Păduraru et al, 2016;Vătămănescu et al, 2019a, b).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, the statistical analysis has shown that SMEs' profitability resulted from international operations (Profits_int variable) and the development of foreign markets where the organization is present (Markets_int variable) are highly correlated with the use of strategic collaborators (Collaborators variable), while the use of intermediaries (Intermediaries variable) correlates solely with the profitability achieved through international operations (Profits_int variable). The current findings are mostly in line with previous research contending the important role of strategic collaborators and intermediaries in achieving profitability at the international level in the case of SMEs (Swoboda, Meierer, Foscht & Morschett, 2011;Capik & Brockerhoff, 2017;Vătămănescu et al, 2020 a, b, c;Vătămănescu et al, 2021). The same applies to the correlation between strategic collaborators and SMEs development on the foreign markets (Păduraru et al, 2016;Vătămănescu et al, 2019a, b).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, strategic cooperation can support small companies to surpass their impediment of being new and minor on the market and take the role of supporter and even advertiser of corporate learning and progress (Comi & Eppler, 2009;Vătămănescu, Alexandru & Andrei, 2015). Strategic partners might become of prime importance to access key information for business development (Capik & Brockerhoff, 2017;Vătămănescu et al, 2020b, Vătămănescu et al, 2021. The network of collaborators allows the SMEs to seize many opportunities in the market and has three main advantages: access to information, speed of information transmission and building the reputation (Håkansson et al, 2009;Andrei & Zaiț, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…They tend to build-up trust-based collaborations gained as a result of integrating rational, emotional and spiritual knowledge when choosing to partner (Bratianu et al, 2021). Engaging in strategic international partnerships, in order to overcome financial burdens and their liability of newness and smallness, to gain brand notoriety and trust, are almost universal reasons for which SMEs decide to forge strong ties to foreign partners (Capik and Brockerhoff, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Business relationships contribute to the transfer of knowledge about the internationalisation process and overseas markets, as well as customer needs and wants (Jahanson & Vahlne, 2009;Soniewicki, 2015), they shape companies' behaviour and actions in the internationalisation process (Coviello & Munro, 1995;Ratajczak-Mrozek, Dymitrowski, & Małys, 2012), often initiating the internationalisation process (Deszczyński, Fonfara, & Dymitrowski, 2017). They facilitate access to resources essential for successful foreign market entry (Dunning, 2015;Blankenburg, 1995) and also limit the risk of failure in international new ventures (Capik & Brockerhoff, 2017). They also seem to influence the speed of innovations implemented in the internationalisation process (Dymitrowski, 2014).…”
Section: Introductionmentioning
confidence: 99%